EFFECT OF PER, EPS, NPM, AND ASSET GROWTH ON STOCK PRICES IN MANUFACTURING COMPANIES IN THE FOOD AND BEVERAGE SUB-SECTOR PERIOD 2016–2020 - Sriyono; Silvi Wulandari Silvi (Universitas Nahdlatul Ulama Sidoarjo, 2022)
This research is a type of quantitative research with hypothesis testing. The data used in this study is in the form of annual reports of manufacturing companies in the food and beverage sub-sector for the period 2016–2020. The number of observations in this study was 688 consisting of 28 manufacturing companies in the food and beverage sub-sector. The sampling technique used0was purposive sampling with several criteria that the researchers determined. The analysis technique used in this research is a multiple linear regression analysis techniques with the help of software for the operating system called eviews version 9.0. The results of this study prove that the Price Earning Ratio (PER) has a significant effect on stock prices; Earning Per Share (EPS) has a significant effect on stock prices; Net Profit Margin (NPM) has a significant effect on stock prices; Asset growth has a significant effect on stock prices.